Proceedings of the ICTs for Improving Patients Rehabilitation Research Techniques 2013
DOI: 10.4108/icst.pervasivehealth.2013.252148
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive Sleep Monitoring using Smartphones

Abstract: How we feel is greatly influenced by how well we sleep. Emerging quantified-self apps and wearable devices allow people to measure and keep track of sleep duration, patterns and quality. However, these approaches are intrusive, placing a burden on the users to modify their daily sleep related habits in order to gain sleep data; for example, users have to wear cumbersome devices (e.g., a headband) or inform the app when they go to sleep and wake up. In this paper, we present a radically different approach for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
148
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(161 citation statements)
references
References 11 publications
0
148
0
Order By: Relevance
“…They evaluated their approach on 10 healthy pilgrims for 18 days. Zhenyu Chen et al [4] presented an approach for measuring sleep duration based on a novel best effort sleep (BES) model. The BES model infers sleep using smartphones in a completely unobtrusive way.…”
Section: Related Workmentioning
confidence: 99%
“…They evaluated their approach on 10 healthy pilgrims for 18 days. Zhenyu Chen et al [4] presented an approach for measuring sleep duration based on a novel best effort sleep (BES) model. The BES model infers sleep using smartphones in a completely unobtrusive way.…”
Section: Related Workmentioning
confidence: 99%
“…Two very different scenarios, which suggest that "sleeping" should be separated into a distinct AC. Arguments against that are again raised through the smartphones sensor possibilities, where several studies have found objective ways to infer sleep (e.g., [32,33]). …”
Section: Activity Categoriesmentioning
confidence: 99%
“…Devices such as Fitbit [84,85] and the Jawbone UP [86,87] are wearable technologies used to allow users to monitor and record their activity levels during exercise and sleep. These devices have no display and no direct connection to the internet, the user can only access the information stored by using the companion app on a tethered mobile device [88,89,90].…”
Section: User Interactionmentioning
confidence: 99%